Screening Tumbuhan Alternatif Penghasil Xanthorrhizol Menggunakan Pendekatan In-Silico Berdasarkan Marker MatK - Diardy Shauman Rachmatan; Topik Hidayat (Fakultas Biologi | Universitas Jenderal Soedirman, 2020)
Xanthorrhizol is a compound that has many uses such as anticancer, antimicrobial, anti-inflammatory, antioxidant, antihyperglycemic, antihypertensive, etc. However, this xanthorrhizol is only found in javanese turmeric (Curcuma zanthorrhiza) where this species only grows well in Indonesia. MatK from the GeneBank NCBI is used to find plants that are closely related to Curcuma zanthorrhiza. Multiple sequence alignment was done using ClustalX 1.83, and phylogenetic analysis was done using PAUP 4.0. The results of the reconstruction of the phylogenetic tree showed that white turmeric (Curcuma zedoaria) was the closest plant related to Curcuma zanthorrhiza. Curcuma zedoaria is a plant commonly found in tropical countries, such as India, Japan and Thailand. In Indonesia Curcuma zedoaria is known as Temu Putih. It is known that the chemical content of Temu Putih rhizome consists of curcuminoids, essential oils, and polysaccharides. Curcuminoid includes: curcumin, demethoxycurcumin, bisdemetoksikurkumin and 1,7-bis (4-hydroxyphenyl) -1,4,6-heptatrien-3-on. Curcuma zedoaria has rich essential oils: starch, curcumin, arabin, gums, etc. There is also more than ten sesquiterpene from Rhizome of Curcuma zedoaria such as furanodiene, furanodienone, zedorone, curzerenone, curzeone, germacrone, 13-hydroxy germacrone, dihydro-curdione, curcumenone and zedoaronediol. Based on that Curcuma zedoaria doesn’t produce xanthorrhizol naturally, but Curcuma zedoaria has a bioactive substance such as sesquiterpene and its closely related to Curcuma zanthorrhiza, genetic engineering can probably be used to produce xanthorrhizol.